Analysis of Coastline Changes in Palu Bay, Central Sulawesi after the 2018 Tsunami Based on Sentinel 1 Satellite Imagery Using the Digital Shoreline Analysis System (DSAS) Method - Fuad, Mochamad Arif Zainul; Hardiansyah, Fikri; Semedi, Bambang (Faculty of Fisheries and Marine, Universitas Riau, 2022)
The Palu-Donggala earthquake that occurred on September 28, 2018 caused additional disasters in the form of liquefaction and tsunami. The tsunami that hit the coastal area of ​​Palu Bay caused considerable damage, indicating a change in the coastline. The purpose of this study was to determine the changes in the coastline that occurred in Palu Bay, Palu City, Central Sulawesi as a result of the Tsunami. The data used in this study are Sentinel 1 satellite imagery before and after the Tsunami occurred. The coastline at each time is obtained from the extraction of Sentinel 1 satellite imagery. Analysis of shoreline change uses quantitative descriptive techniques with the help of the DSAS tool with change analysis based on the Net Shoreline Movement (NSM) method which is integrated with ArcGIS software. The results show that there has been a significant change in the coastline in Palu Bay, Palu City, Central Sulawesi. Coastline changes that occur are in the form of abrasion and accretion conditions, but are more dominated by abrasion. The highest abrasion of -167.53m is found on transect 309 which is located in the District of Mantikulore, and the lowest abrasion value of -0.43m is found on transect 242 which is located in the Ulujadi District. Meanwhile, the highest accretion value of 47.27m is found on transect 105 which is located in the West Palu District, and the lowest abrasion value of 0.56m is found on transect 68 which is also located in the West Palu District. The magnitude of the change in coastline that occurred in Palu Bay, Palu City, Central Sulawesi after the Tsunami was influenced by the openness of the coastal area to wave blows, the oval and narrow morphology of Palu Bay and the occurrence of ground deformation in the Palu-Koro Fault.